Ambiguity and its effects on organizations. A literature review - Ordoñez Abril, Daniel Yiwady (2021)
Ambiguity develops in confusing organizational environments that require leaders and/or managers to implement methodologies, strategies, competencies and skills that promote good labor relations, increased productivity and sustainability in the market. This article proposes to systematically review the literature on ambiguity in organizations and its impact on social development. It shows that this environment can be developed in any context, it has no established techniques or strategies, but it is necessary for the people in charge to have leadership, make sound decisions, manage ambiguous situations and be creative and innovative in the face of emerging situations. This research concludes that in chaotic contexts where situations of ambiguity are continuously presented, it is vital that the leaders of organizational processes have soft and hard skills that allow them to effectively face the conditions of the context and mitigate psychosocial risks.